2003
DOI: 10.1002/ana.10684
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis‐associated hearing loss: Protection by adjunctive antioxidant therapy

Abstract: Hearing loss is the most frequent long-term complication of pneumococcal meningitis, affecting up to 40% of survivors. Unfortunately, adjuvant therapy with dexamethasone has failed to satisfactorily reduce its incidence. Therefore, we evaluated the use of antioxidants for the adjunctive therapy of meningitis-associated deafness. Eighteen hours after intracisternal injection of 7.5 x 10(5) colony-forming units of Streptococcus pneumoniae, rats were treated systemically either with ceftriaxone and the antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 37 publications
3
46
0
3
Order By: Relevance
“…Furthermore, TLR and MyD88 knockout mice demonstrated less hearing loss following pneumococcal meningitis (247). In a rat model, cochlear expression of iNOS and eNOS was upregulated following pneumococcal meningitis, and RNS-mediated cochlear damage could be attenuated both electrophysiologically and histopathologically by RNS scavengers (227,241,243). Earlier studies with guinea pigs showed that local perfusion of the scala tympani with NO donor compounds resulted in cochlear damage and could be attenuated by NO inhibitors or O 2 scavengers (14).…”
Section: Cochlear Damage and Hearing Lossmentioning
confidence: 99%
“…Furthermore, TLR and MyD88 knockout mice demonstrated less hearing loss following pneumococcal meningitis (247). In a rat model, cochlear expression of iNOS and eNOS was upregulated following pneumococcal meningitis, and RNS-mediated cochlear damage could be attenuated both electrophysiologically and histopathologically by RNS scavengers (227,241,243). Earlier studies with guinea pigs showed that local perfusion of the scala tympani with NO donor compounds resulted in cochlear damage and could be attenuated by NO inhibitors or O 2 scavengers (14).…”
Section: Cochlear Damage and Hearing Lossmentioning
confidence: 99%
“…Possibly, the difference of the power of NAC to reduce the otologic sequelae may be related to differences in the animal models used. Indeed, compared with the hearing thresholds in uninfected control animals, the hearing thresholds were elevated by 60 dB in rats with meningitis (25), whereas the hearing thresholds were up to 90 dB higher in mice with meningitis (current study). This may be related to a higher vulnerability of mice to cochlear damage, as evidenced by differences in histopathology.…”
Section: Discussionmentioning
confidence: 48%
“…For example, infected mice often develop hemorrhages in the spiral ganglion, which are usually not found in rats with pneumococcal meningitis-associated hearing loss (29,40). Also, different pneumococcal serotypes were used in the two experimental setups, namely, serotype 3 in the rat model (25) and serotype 2 in this current mouse model. As differences in pneumococcal serotype are known to account for differences in the development of hearing loss in adults with pneumococcal meningitis (41) and pathophysiologic alterations in animal models of pneumococcal meningitis (42), this may have added further to the variations seen between the two models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations